Neurons of the Dopaminergic/Calcitonin Gene-Related Peptide A11 Cell Group Modulate Neuronal Firing in the Trigeminocervical Complex: An Electrophysiological and Immunohistochemical Study - Charbit, Annabelle R. (J Neurosci, 2009)
Activation of spinal trigeminal afferents innervating the cranial vasculature is likely to play a role in migraine, although some parts of the clinical presentation may have a dopaminergic basis. The A11 nucleus, located in the posterior hypothalamus, provides the only known source of descending dopaminergic innervation for the spinal gray matter. Extracellular recordings were made in the trigeminocervical complex (TCC) in response to electrical stimulation of the dura mater. Receptive fields were characterized by mechanical noxious and innocuous stimulation of the ipsilateral ophthalmic dermatome. Stimulation of the A11 significantly inhibited peri-middle meningeal artery dural and noxious pinch evoked firing of neurons in the TCC. This inhibition was reversed by the D(2) receptor antagonist eticlopride. Lesioning of the A11 significantly facilitated dural and noxious pinch and innocuous brush evoked firing from the TCC. In previous work using immunohistofluorescence, it was shown that D(1) and D(2) receptors were found in the rat TCC, and here we report, in addition, that D(4) and D(5) dopamine receptors are also present, whereas D(3) receptors are not. No dopamine receptors were present in the A11 nucleus itself. However, the A11 does contain dopamine and calcitonin gene-related peptide (CGRP) and, by this combination, is distinct from the neighboring CGRPergic subparafascicular nucleus. Exploration of dopaminergic influences and mechanisms in migraine may open up an almost untapped opportunity to pursue potential new therapeutic options for the disorder.